2007
DOI: 10.1111/j.1469-0691.2007.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal spread of SCCmec type IV methicillin-resistant Staphylococcus aureus between community and hospital

Abstract: The staphylococcal chromosome cassette (SCC)mec types of 382 hospital-acquired methicillin-resistant Staphylococcus aureus (HA-MRSA) isolates in Taiwan were analysed over a 7-year period (1999-2005). There was an abrupt increase in SCCmec type IV in HA-MRSA during 2005. The molecular epidemiology of a subset (n = 69) of HA-MRSA isolates with SCCmec types III, IV or V was characterised and compared with that of community-acquired MRSA (CA-MRSA) (n = 26, collected during 2005). Pulsed-field gel electrophoresis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 39 publications
3
61
0
1
Order By: Relevance
“…It has been found in CA-MRSA isolates predominantly in Australia (670) and Taiwan (411,414,975). SCCmec type V is rare in Europe and the United States.…”
Section: Sccmec Types IV and V In Ca-mrsa Isolatesmentioning
confidence: 99%
“…It has been found in CA-MRSA isolates predominantly in Australia (670) and Taiwan (411,414,975). SCCmec type V is rare in Europe and the United States.…”
Section: Sccmec Types IV and V In Ca-mrsa Isolatesmentioning
confidence: 99%
“…The CA-MRSA strains that have spread most rapidly belong to one of five clonal groups and are associated with specific STs in each case, i.e., ST1 (corresponding to the USA400 clonal group) (48,66), ST8 (USA300 and USA500) (7,15,21,25,33), ST59 (USA1000) (30,68), ST80 (Europe) (66), and ST30 (Pacific) (15,48). Although not absolute (57), an association between the clinical spectrum of infections caused by CA-MRSA and the presence of Panton-Valentine leukocidin (PVL) genes, which code for the production of cytotoxins that cause tissue necrosis and leukocyte destruction, has been noted (24).…”
Section: Vol 192 2010mentioning
confidence: 99%
“…In three Czech strains of S. aureus, the presence of lukS-PV a lukF-PV genes were determined by the National Reference Laboratory in the year 2004 and found to belong to CA-MRSA 56 . Antimicrobial resistance tests and selected methods of molecular biology demonstrated that their characteristics diff er from the multi-drug resistant HA-MRSA strains described in hospital patients 14,39,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] .…”
Section: Current Knowledge Of Methicillin-resistant Staphylococcus Aumentioning
confidence: 99%